1999
DOI: 10.1037/0003-066x.54.9.755
|View full text |Cite
|
Sign up to set email alerts
|

When interventions harm: Peer groups and problem behavior.

Abstract: This article explored developmental and intervention evidence relevant to iatrogenic effects in peer-group interventions. Longitudinal research revealed that "deviancy training " within adolescent friendships predicts increases in delinquency, substance use, violence, and adult maladjustment. Moreover, findings from 2 experimentally controlled intervention studies suggested that peer-group interventions increase adolescent problem behavior and negative life outcomes in adulthood, compared with control youth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
1,068
9
36

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,646 publications
(1,161 citation statements)
references
References 59 publications
48
1,068
9
36
Order By: Relevance
“…This phenomenon has been reported elsewhere for peer‐led and multi‐component youth programmes 63, 64, particularly among high‐risk groups 63. Similarly, in the two studies in our review, the effect was attributed to involvement with existing networks of substance‐using peers in one study 20, while in the other it was noted that increased rates of smoking were observed among those with pro‐smoking attitudes and a substantial proportion of tobacco‐using friends 62.…”
Section: Implications and Other Evidencesupporting
confidence: 86%
“…This phenomenon has been reported elsewhere for peer‐led and multi‐component youth programmes 63, 64, particularly among high‐risk groups 63. Similarly, in the two studies in our review, the effect was attributed to involvement with existing networks of substance‐using peers in one study 20, while in the other it was noted that increased rates of smoking were observed among those with pro‐smoking attitudes and a substantial proportion of tobacco‐using friends 62.…”
Section: Implications and Other Evidencesupporting
confidence: 86%
“…Relationships can provide a compelling source of influence, and this study emphasizes the importance of considering the relationships of adolescents even when prevention and intervention efforts are focused on individual behavior. We caution, however, against aggregating youth in intervention programs, because there is evidence for short-and long-term iatrogenic effects on problem behavior with high-risk youth resulting from these peer group type interventions (Dishion et al, 1999). Model 2: Prediction with negative interaction as a mediator of delinquent peer association.…”
Section: Implications For Application and Public Policymentioning
confidence: 99%
“…Capaldi and Crosby (1997) found assortative partnering by antisocial behavior in late adolescence for the OYS men and their romantic partners. Although midadolescent association with delinquent peers was predictive of negative engagement with others in late adolescence, negative interaction or poor social skills did not appear to be involved in maintaining the association with delinquent peers into young adulthood.Given that antisocial talk took place across three different types of late-adolescent relationships and that delinquency training has been associated with increases in delinquent behavior (Dishion et al, 1999), this antisocial talk appears to be an important and generally overlooked social influence process. This may help to explain why it is difficult to intervene effectively in interrupting the development of delinquency in adolescence (Thornberry & Krohn, 1997).…”
mentioning
confidence: 99%
“…In suicide prevention, concerns have been raised that even discussing suicide may direct non-affected youth towards these outcomes (some evidence now refutes this; see Gould et al, 2005), but poorly conceived programs that memorialize peers who have recently committed suicide may have a contagion effect. In delinquency and drug prevention, there is clear evidence of learning that is transmitted from more deviant to less deviant youth (Dishion et al, 1996(Dishion et al, , 1999(Dishion et al, , 2001. Only by studying the impact among these different subgroups in carefully designed randomized trials will we be able to determine whether a program is having a harmful effect on a vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to programs that isolate and concentrate poorly behaving youth (Dishion et al, 1996(Dishion et al, , 1999(Dishion et al, , 2001, such approaches provide benefit by shaping behaviors within the most relevant social fields in their lives, thereby avoiding issues of labeling children as different and requiring a different intervention to adjust for reentry. These early, universal preventive interventions are likely to be cost effective strategies for preventing the lifepersistent conduct disorder and antisocial behavior.…”
Section: Discussionmentioning
confidence: 99%